Impact of two non-nutritive sucking patterns on the development of anterior open bite in children of two kindergartens in Baghdad city - Munad J Al Duliamy (College of Dentistry/ University of Baghdad, 2020)
Background: Non-nutritive sucking habit (NNSH) is the main environmental causative factor that disturbs normal orofacial development. In spite of the harmful effect of pacifier as a NNSH, mothers aware from the other types of NNSH like thumb sucking far more than pacifier use. Open bite is one of the most challenging malocclusions in orthodontics due to the high prevalence of relapse after treatment, so preventing the causative factor of its occurrence is essential at early age of child life. This study aims to assess the impact of two non-nutritive patterns on the development of anterior open bite in primary dentition and to compare which of these habits mostly affect open bite development. Materials and Methods: The sample consisted of 313 Iraqi children (135 boys, 178 girls), aged 3-5 years, enrolled at two public kindergartens in Baghdad city, the Capital of Iraq. A pre-tested questionnaire with clinical examination were used to obtain data regarding thumb sucking, pacifier and the presence of open bite. Excel sheets were used for data processing, and Chi square test was used in data analysis. Results: There was a significant association between NNSH and the development of open bite (p value = 0.01). No gender differences in open bite prevalence were observed. The prevalence of non-nutritive sucking habits and open bite was 63.11% and 52.9% respectively with no gender difference. There was no significant differences between the effect of pacifier and thumb sucking habits on the development of an anterior open bite. Conclusion: Both pacifier and thumb sucking at preschool age are significant causative factors that lead to development of open bite in primary dentition. Encouraging mothers to ban and discontinue pacifier and thumb sucking habits as early as possible in the child's life is a crucial factor to prevent open bite development. On the other hand if general health of the child indicates the use of pacifier, mothers should use an orthodontic pacifier and for short time.